Physical properties and optical-infrared transmission spectrum of the giant planet XO-1 b. Issue 3 (11th September 2018) - Southworth, John; Tregloan-Reed, J; Pinhas, A; Madhusudhan, N; Mancini, L; Smith, A M S
ABSTRACT: We present 10 high-precision light curves of four transits in the XO-1 planetary system, obtained using u, g, r, redshifted H α, I, and $z$ filters. We use these to measure the physical properties, orbital ephemeris, and a transmission spectrum of the planet covering the full optical wavelength range. We augment this with published HST /WFC3 observations to construct a transmission spectrum of the planet covering 0.37–1.65 $μ$ m. Our best-fitting model to this spectrum is for a H2 /He-rich atmosphere containing water (3.05σ confidence), nitrogen-bearing molecules NH3 and HCN (1.5σ) and patchy cloud (1.3σ). We find that adding the optical to the near-infrared data does not lead to more precise constraints on the planetary atmosphere in this case. We conduct a detailed investigation into the effect of stellar limb darkening on our results, concluding that the choice of limb darkening law and coefficients is unimportant; such conclusions may not hold for other systems so should be reassessed for all high-quality data sets. The planet radius we measure in the g band is anomalously low and should be investigated with future observations at a higher spectral resolution. From the measured times of transit, we determine an improved orbital ephemeris, calculate a lower limit on the modified stellar tidal quality factor of $Q_\star ^{\, ′ } \gt 10^{5.6}$, and rule out a previously postulated sinusoidal variation in the transit times.